2017
DOI: 10.3389/fnhum.2016.00686
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Distribution of Mesencephalic Astrocyte-Derived Neurotrophic Factor in the Retina and Optic Nerve

Abstract: Mesencephalic astrocyte-derived neurotrophic factor (MANF), otherwise named Arginine-Rich, Mutated in Early-stage Tumors (ARMET), is a secretory endoplasmic reticulum stress (ERS) protein that is widely expressed in mammalian tissues. To date, little is known about the distribution and expression of MANF in the retina and optic nerve (ON). Therefore, we studied the expression and distribution of MANF in the ON and retina by real-time PCR, immunofluorescence staining and western blotting. Results from rat and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 38 publications
3
4
0
Order By: Relevance
“…As we have previously described Gao et al (2017) , immunofluorescence staining shows that MANF is predominantly localized in the ganglion cell layer and inner nuclear layer in both rat and human retinas ( Figures 1A,B ). To determine if the MANF expression in the ganglion cell layer was specific to the RGCs, primary cultured RGCs were used for in vitro validation.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…As we have previously described Gao et al (2017) , immunofluorescence staining shows that MANF is predominantly localized in the ganglion cell layer and inner nuclear layer in both rat and human retinas ( Figures 1A,B ). To determine if the MANF expression in the ganglion cell layer was specific to the RGCs, primary cultured RGCs were used for in vitro validation.…”
Section: Resultssupporting
confidence: 74%
“…Recently, studies conducted at the University of Helsinki demonstrated that the concentration of MANF is increased in the serum in children with type 1 diabetes, which indicated that MANF may be used as a potential therapeutic protein for diabetes ( Galli et al, 2016 ). Furthermore, our recent studies showed that MANF could be robustly expressed in RGCs and that hypoxia can stimulate the up-regulation of MANF expression over time, which suggested that MANF may play a vital role in the functional regulation of RGCs in both health and disease ( Gao et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, MANF has been implicated in several nervous system disorders 17,22 . Furthermore, several reports have determined that MANF promotes optic nerve survival and plays a role in ophthalmic diseases 23‐25 . In this study, we have shown that MANF might play an important role in extension of neurites and cell death in RGCs.…”
Section: Discussionsupporting
confidence: 57%
“…Recent reports have indicated that MANF protects dopaminergic neurons and other cell types in animal models of Parkinson's disease, Alzheimer's disease and brain ataxia 17,22 . Although several reports have shown that MANF is associated with optic nerve survival and ophthalmic diseases, 23‐25 little is known about the neuroprotective function of MANF for RGC survival in glaucoma.…”
Section: Introductionmentioning
confidence: 99%
“…MANF is expressed in the human retina and optic nerve (35), and it protects retinal ganglia cells from hypoxia and apoptotic injury in vitro and in vivo (36). MANF in D. melanogaster (DmMANF) was also found to be expressed in the fly visual system neurons and glia, and its removal caused degeneration of glial cells (37).…”
Section: Effects In Other Neurodegenerative Diseasesmentioning
confidence: 99%